Physician Practices Regarding SIDS in Kansas. (July 2017) - Thornhill-Scott, Fannette; Dong, Frank; Redmond, Michelle; Ablah, Elizabeth
Sudden infant death syndrome (SIDS) is the leading cause of death among infants aged 1 to 12 months. The purpose of this study was to assess prenatal and postnatal physicians' knowledge about SIDS in a county with high rates of SIDS deaths. A cross-sectional survey was conducted of pediatricians, family practitioners, and obstetricians in Sedgwick County, Kansas. Most physicians reported correctly that there were effective measures to reduce SIDS. Most respondents agreed it was important to discuss SIDS with parents. Pediatricians were more likely than family practitioners and obstetricians to recognize that pacifier use is important for infants in their first year to reduce SIDS and 2 to 4 months is the age range for peak incidence of SIDS. Pediatricians, family practitioners, and obstetricians are knowledgeable about SIDS and SIDS risk reduction. However, they are not allocating adequate time for discussing SIDS and SIDS reduction efforts with patients.